Uterine Immunity and Microbiota: A Shifting Paradigm - Agostinis, Chiara; Mangogna, Alessandro; Bossi, Fleur; Ricci, Giuseppe; Kishore, Uday; Bulla, Roberta (Frontiers in Immunology, 2019)
The female reproductive tract harbors distinct microbial communities, as in the vagina, cervical canal, uterus, and fallopian tubes. The nature of the vaginal microbiota is well known; in contrast, the upper reproductive tract remains largely unexplored. Alteration in the uterine microbiota, which is dependent on the nutrients and hormones available to the uterus, is likely to play an important role in uterine-related diseases such as hysteromyoma, adenomyosis, and endometriosis. Uterine mucosa is an important tissue barrier whose main function is to offer protection against pathogens and other toxic factors, while maintaining a symbiotic relationship with commensal microbes. These characteristics are shared by all the mucosal tissues; however, the uterine mucosa is unique since it changes cyclically during the menstrual cycle as well as pregnancy. The immune system, besides its role in the defense process, plays crucial roles in reproduction as it ensures local immune tolerance to fetal/paternal antigens, trophoblast invasion, and vascular remodeling. The human endometrium contains a conspicuous number of immune cells, mainly Natural Killers (NK) cells, which are phenotypically distinct from peripheral cytotoxic NK cells and macrophages. The endometrium contains also few lymphoid aggregates comprising B cell and CD8+ T cells. The number and the phenotype of these cells change during the menstrual cycle. It has become evident in recent years that the immune cell phenotype and function can be influenced by microbiota. Immune cells can sense the presence of microbes through their pattern recognition receptors, setting up host-microbe interaction. The microbiota exerts an appropriately controlled defense mechanism by competing for nutrients and mucosal space with pathogens. It has recently been considered that uterus is a non-sterile compartment since it seems to possess its own microbiota. There has been an increasing interest in characterizing the nature of microbial colonization within the uterus and its apparent impact on fertility and pregnancy. This review will examine the potential relationship between the uterine microbiota and the immune cells present in the local environment.